NOTCH1 activation clinically antagonizes the unfavorable effect of PTEN inactivation in BFM-treated children with precursor T-cell acute lymphoblastic leukemia - Bandapalli, Obul Reddy; Zimmermann, Martin; Kox, Corinne; Stanulla, Martin; Schrappe, Martin; Ludwig, Wolf-Dieter; Köhler, Rolf; Muckenthaler, Martina; Kulozik, Andreas (Haematologica, the hematology journal, 2013)
Despite improvements in treatment results for pediatric T-cell acute lymphoblastic leukemia, approximately 20% of patients relapse with dismal prognosis. PTEN inactivation and NOTCH1 activation are known frequent leukemogenic events but their effect on outcome is still controversial. We analyzed the effect of PTEN inactivation and its interaction with NOTCH1 activation on treatment response and long-term outcome in 301 ALL-BFM treated children with T-cell acute lymphoblastic leukemia. We identified PTEN mutations in 52 of 301 (17.3%) of patients. In univariate analyses this was significantly associated with increased resistance to induction chemotherapy and a trend towards poor long-term outcome. By contrast, patients with inactivating PTEN and activating NOTCH1 mutations showed marked sensitivity to induction treatment and excellent long-term outcome, which was similar to patients with NOTCH1 mutations only, and more favorable than in patients with PTEN mutations only. Notably, in the subgroup of patients with a prednisone- and minimal residual disease (MRD)-response based medium risk profile, PTEN-mutations without co-existing NOTCH1-mutations represented an MRD-independent highly significant high-risk biomarker. Mutations of PTEN highly significantly indicate a poor prognosis in T-ALL patients who have been stratified to the medium risk group of the BFM-protocol. This effect is clinically neutralized by NOTCH1 mutations. Although these results have not yet been explained by an obvious molecular mechanism, they contribute to the development of new molecularly defined stratification algorithms. Furthermore, these data have unexpected potential implications for the development of NOTCH1 inhibitors in the treatment of T-cell acute lymphoblastic leukemia in general, and in those with a combination of PTEN and NOTCH1 mutations in particular.
Gesehen am 28.10.2020